2002
DOI: 10.1021/jp0143645
|View full text |Cite
|
Sign up to set email alerts
|

Competition between X···H···Y Intramolecular Hydrogen Bonds and X····Y (X = O, S, and Y = Se, Te) Chalcogen−Chalcogen Interactions

Abstract: High-level G2(MP2) ab initio and B3LYP/6-311+G(3df,2p) density functional calculations have been carried out for a series of β-chalcogenovinylaldehydes, HC(X)−CHCH−CYH (X = O, S; Y = Se, Te). Our results indicate that for X = O, S and Y = Se, the O−H···Se and the S−H···Se intramolecular hydrogen bonds compete in strength with the O···Se and the S···Se interaction, while the opposite is found for the corresponding tellurium-containing analogues. The different strength of O−H···Se and O···H−Se intramolecular h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
120
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(126 citation statements)
references
References 55 publications
6
120
0
Order By: Relevance
“…Although a few ␤-oxo selenocarbonyl compounds have been isolated as stable compounds [13], their tautomerization has not been reported. On the other hand, theoretical studies on ␤-oxo selenoaldehydes have suggested that their enol forms and eneselenol forms are energetically close [14].…”
Section: Resultsmentioning
confidence: 99%
“…Although a few ␤-oxo selenocarbonyl compounds have been isolated as stable compounds [13], their tautomerization has not been reported. On the other hand, theoretical studies on ␤-oxo selenoaldehydes have suggested that their enol forms and eneselenol forms are energetically close [14].…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] It belongs to the family of s-hole bonding, where the halogen bond (X-bond) is by far the most known. Since chalcogen atoms are electronegative elements, they are usually negatively charged in organic compounds.…”
mentioning
confidence: 99%
“…For Te-containing compounds, we used the SKBJ relativistic potential of Stevens et al, [42] which accounts for the most important relativistic effects in conjunction with the basis set proposed by Sanz et al [43] For geometry optimizations and harmonic frequency calculations the aforementioned effective core potential was used together with the [4,1] + d basis for Te, [43] whereas for the first-, second-, and third-row atoms, a 6-31G(d) basis set was adopted. Hereafter, for the sake of simplicity we will refer to this basis set as 6-31G(d).…”
mentioning
confidence: 99%
“…Hereafter, for the sake of simplicity we will refer to this basis set as 6-31G(d). The corresponding final energies were evaluated by using the (6 s,6p,3d,1f) G2-type basis set [43] for Te and a 6-311 + G(3df,2p) basis set expansion for the remaining atoms of the system. Again for the sake of simplicity the (6 s,6p,3d,1f) basis for Te will be named hereafter as a 6-311 + G(3df,2p) basis.…”
mentioning
confidence: 99%